Characterization of material properties of renewable biobased powder for 3D printing using the traditional moulding sand test methods of foundry technology - Abdulkader Ali Kadauw; Tillmann Bohme; Henning Zeidler (Zanco Journal of Pure and Applied Sciences)
Bio-based powders are produced from renewable resources such as plants, agricultural waste, or even algae. These materials offer a compelling alternative to conventional plastics, which are often obtained from fossil fuels. New types of powder materials for the 3D printing process need to be characterised. They play an important role in 3D printing technology. Based on the results from testing, process parameters can be adjusted. There are currently no standardised methods for the testing of 3D printing materials. The moulding sand material has the same material properties as the renewable bio-based powders used for 3D printing.